Physical Activity, Obesity and Self-Esteem in Chilean Schoolchildren [Actividad Física, Obesidad y Autoestima en Escolares Chilenos: Análisis Mediante Ecuaciones Estructurales] - Cofre-Bolados, C (Sociedad Medica de Santiago, 2017)
Background: Obesity is a worldwide epidemic disease and a problem for the Chilean society. Aim: To analyze the relationship between physical condition, body mass index (BMI), level of physical activity and self-esteem. Material ad Methods: Questionnaires to assess self-esteem (Rosemberg scale) and levels of physical activity (Physical Activity Questionnaire for older Children, PAQ-C) were answered by 515 children aged 10.5 ± 0.5 years from 27 schools of Santiago de Chile. BMI was calculated. Course-Navette test was carried out, vertical jump and hand dynamometry were measured. For statistical analysis, structural equations were used. Results: An acceptable goodness of fit for the models was found. There was a positive relationship between BMI and hand dynamometry, as well as a negative relationship between BMI and maximal oxygen consumption, jumping ability, physical activity and self-esteem. Finally, self-esteem was positively related to physical activity engagement. Conclusions: In these children, self-esteem was related to physical activity variables. © 2017, Sociedad Medica de Santiago. All rights reserved.